2002
DOI: 10.1136/fn.86.1.f32
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extubation failure in preterm infants

Abstract: Objective: To identify whether the results of assessment of respiratory muscle strength or respiratory load were better predictors of extubation failure in preterm infants than readily available clinical data. Patients: Thirty six infants, median gestational age 31 (range 25-36) weeks and postnatal age 3 (1-14) days; 13 were < 30 weeks of gestational age. Methods: Respiratory muscle strength was assessed by measurement of maximum inspiratory pressure generated during airway occlusion, and inspiratory load was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
5
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 16 publications
6
55
5
16
Order By: Relevance
“…10 In some studies we verified variable rates in relation to extubation failure, sometimes associated with lower birth weight and gestational age. 1, 15,20,21 As such, we sought to verify if there was a relationship between extubation failure in the two methods and the BW and GA, classification of the premature infant, and the MV time. We found that there was no significant difference between the association of the characteristics described and the methods under study.…”
Section: Discussionmentioning
confidence: 99%
“…10 In some studies we verified variable rates in relation to extubation failure, sometimes associated with lower birth weight and gestational age. 1, 15,20,21 As such, we sought to verify if there was a relationship between extubation failure in the two methods and the BW and GA, classification of the premature infant, and the MV time. We found that there was no significant difference between the association of the characteristics described and the methods under study.…”
Section: Discussionmentioning
confidence: 99%
“…These data have show increased extubation failure risk for higher FiO 2 and lower current body weight. Hermeto et al (15) have shown a 23% extubation failure rate in a population with birth weight < 1,250 g and 35% with birth weight < 1,000 g. Additionally, the Dimitriou et al (4) study has shown that neonates with lower birth weight (among other factors) and pre-extubation higher FiO 2 were associated with extubation failure.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies confirm our results, indicating among the main failure causes apnea and increased respiratory load. (4,16) Sinha and Donn (29) say that children with no respiratory distress or worsened gas exchange during the test had between 60% to 80% chance to require no artificial airway support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations